Selected strong decay modes of Y (4260); Physical Review D; Vol. 89, iss. 3 - Yubing Dong; Faessler A. Amand; Gutsche Th. Gutsche; Lyubovitskiy (Lyubovitskij) V. E. Valery Efimovich (2014, 2014)
Title screen